Frequency division sensor signal by controlled and interfering parameters - T. G. Hasanov; E. Z. Batmanov; M. R. Guseinov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is the possibility of obtaining the impedance of the controlled and interfering parameters using the example of a capacitor sensor. Method. The study is based on the determination of the analytical relationship between the change in the impedance of the sensor and the frequency of the current in which the capacitance of the capacitor is excited. Result. Having determined the resistance of individual circuit elements, you can find the impedance of the equivalent circuit at any fixed frequency. An equation for the impedance of the sensor is obtained, reflecting the dependence of the output signal on the change in both the controlled humidity and the interfering parameter - the dielectric constant of oil at any frequency in the studied range. The existence of the frequency parameter for the separation of information contained in the output signal of the measuring circuit has been proved. Conclusion. If the parametric separation of the signal is possible, the output value of the sensor can be automatically corrected for the change in the dielectric constant of the "dry" oil, and continuous measurement of the controlled moisture can be carried out.